Diseño e implementación de un sistema para obtener reportes estadísticos en el departamento de control de calidad de la empresa Novacero S.A - Tapia Chacon, Sonia Elizabeth (2008)
Nowadays the development of software is one of the most used activity that permits to the human being simplifies task that he does daily. It this want development of software for the department of Control of Quality of the NOVACERO S.A enterprise helps to take correct decisions to the managment level. This thesis is formed for three chapters. A first chapter in where is described the concepts and Basic fundations use for the development of the proyect, A second chapter that contains the interpretation of result of the surveys made employers of the enterprise, as the directives of it.